Association between molecular markers linked to the Leptin gene and weight gain in postpartum beef cows Associação entre marcadores moleculares ligados ao gene da Leptina e ganho de peso em vacas de corte no pós-parto - Sabrina Esteves Matos Almeida; Erik Amazonas de Almeida; Gustavo Terra; Jairo Pereira Neves; Paulo Bayard Dias Gonçalves; Tania de Azevedo Weimer (Ciência Rural, 2007)
Three short tandem repeats (STRs), BMS1074, BM1500, IDVGA-51, and three single nucleotide polymorphisms (SNPs), LEPSau3AI (A/B), LEPSau3AI (+/-) and LEPKpn2I linked to the LEP gene were investigated to verify associations with productive performance in postpartum cows of two beef cattle breeds, Aberdeen Angus (AA, n=98) and Charolais (C, n=83). After polymerase chain reaction, STRs were analyzed by vertical electrophoresis and SNPs in agarose gel after endonucleases cleavage. In AA herd 79% of BMS1074*151 carriers had a lower average daily weight gain (ADG) when compared with the population mean daily weight gain (103g), while 62% of BMS1074*151 non-carriers presented a higher ADG (P<0.01); AA animals with at least one BMS1074*151 allele showed a ADG about 159g lower than that of other animals (P<0.01). In both herds, carriers of the BM1500*136 allele presented higher ADG (about 75g day-1 higher in AA, P<0.05, and 96g day-1 in C, P<0.10); animals with one BM1500*136 allele had about a 3-fold higher chance of having a higher ADG than non-cariers, in both populations. Foram investigadas três repetições curtas em tandem (STRs), BMS1074, BM1500 e IDVGA-51 e três polimorfismos de um único nucleotídeo (SNPs) LEPSau3AI (A/B), LEPSau3AI (+/-) e LEPKpn2I, ligados ao gene da leptina, verificando-se associações com o desempenho produtivo em vacas no pós-parto, em dois rebanhos de gado de corte, Aberdeen Angus (AA, n=98) e Charolês (C, n=83). Após a reação em cadeia da polimerase, os STRs foram analisados em géis de poliacrilamida e os SNPs em gel de agarose, após a clivagem com endonucleases. Na raça AA, 79% dos portadores do alelo BMS1074*151 apresentaram ganho médio de peso diário (ADG) menor, quando comparados com a média da população (103g), enquanto 62% dos não-portadores mostraram ADG mais alto (P<0,01); os animais AA com pelo menos um alelo BMS1074*151 possuem ADG cerca de 159g menor que os outros animais (P<0,01). Em ambos os rebanhos, portadores do alelo BM1500*136 apresentaram ADG mais alto (em torno de 75g dia-1 em AA, P<0,05 e 96g dia-1 em C, P<0,10) e animais com um alelo BM1500*136 possuem cerca de três vezes mais chance de ter um ADG maior que os não-portadores.